The effect of zinc‐carbonate hydroxyapatite versus fluoride on enamel surfaces after interproximal reduction. Issue 3 (28th October 2013) - Alessandri Bonetti, G.; Pazzi, E.; Zanarini, M.; Marchionni, S.; Checchi, L.
Summary The aim of this study was to qualitatively investigate the effects of a zinc‐carbonate hydroxyapatite (Zn‐CHA) containing toothpaste on stripped enamel morphology in a pH cycling model in vitro and to compare the efficacy of this toothpaste versus fluoride one which still represent the gold standard to remineralize early enamel lesions. Twenty‐one extracted lower incisors underwent to interproximal enamel reduction with metal strips (Horico 80 µm) on both mesial and distal surfaces. They were then sliced into mesial and distal halves and the 42 samples obtained were randomly assigned to 3 groups of 14 enamel specimens each. For 8 days, teeth were placed in lactic acid solution for 2 h three times a day with 2 h distilled water preservation in between. After each demineralization bath, samples of Group A were brushed with Zn‐CHA containing toothpaste while samples of Group B were brushed with 1, 400 ppm fluoride dentifrice for 5 min before immersion into water. Group C of untreated samples served as control. All the samples were then prepared for scanning electron microscopy (SEM) analysis. A score rating system was used to perform a non‐parametric statistical analysis. No statistically significant differences were found between the samples brushed with fluoride toothpaste and those untreated (Groups B and C) where the highest grade of damage was found, while the lowest grade was recorded in the samples brushed with Zn‐CHA (Group A) and there was a statistically significant difference between this group and the other two groups. SCANNING 36:356–361, 2014. © 2013 Wiley Periodicals, Inc.